Revitalisasi Estetika Fungsional: Eksplorasi Sepeda Roda Tiga Berbasis Material Daur Naik Sebagai Karya Seni Rupa Kontemporer - Ananta Hari Noorsasetya; Prayanto Widyo Harsanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Contemporary art continues to expand its definition, blurring the boundaries between functional objects and fine art. This practice-based research explores the potential of recycled materials in visual art creation, using a tricycle as the primary medium. Using a mixed-media approach, primarily utilizing recycled metal and plate, along with recycled components such as drills and old water pumps, this project aims to transform the tricycle from a mobility object into a work of fine art. This concept intentionally blurs functional aesthetics, emphasizing freedom of expression and uniqueness of form, and reflecting a dialogue between the past and the present through recycled materials. Through a case study of the work